2021
DOI: 10.1519/ssc.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and Application of Athlete Monitoring Programs in National Collegiate Athletic Association Women's Soccer: A Narrative Review

Abstract: National Collegiate Athletic Association (NCAA) women's soccer players spend 2–3 weeks in preseason, followed by 12–14 weeks in the competitive season. Because of a short, intense preseason followed by the long competitive season, athlete monitoring programs would play an important role in maximizing physical preparation and match performance while minimizing unfavorable adaptations and fatigue during the NCAA Division I collegiate women's soccer competitive season. Athlete monitoring measures can be used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 74 publications
(307 reference statements)
1
28
0
1
Order By: Relevance
“…The benefits of ETL are (a) the quantification of match performance (8,22,41) and (b) the manipulation of ETL to a matchplay (7,21). In addition to ITL and ETL measures, competitive soccer teams incorporate response assessments including subjective wellness and isometric and dynamic neuromuscular performance measured by force plates (6,11,17,18,44). These measures provide practitioners (e.g., strength and conditioning coaches, sports scientists, and sports medicine staff) assessments of player's subjective and objective physical readiness to train or play.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of ETL are (a) the quantification of match performance (8,22,41) and (b) the manipulation of ETL to a matchplay (7,21). In addition to ITL and ETL measures, competitive soccer teams incorporate response assessments including subjective wellness and isometric and dynamic neuromuscular performance measured by force plates (6,11,17,18,44). These measures provide practitioners (e.g., strength and conditioning coaches, sports scientists, and sports medicine staff) assessments of player's subjective and objective physical readiness to train or play.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of an athlete monitoring program would be useful to develop physical and psychological preparation of the player in NCAA soccer. Athlete monitoring programs primarily aim to maximize sports performance and improve program efficacy while minimize fatigue during the competitive season (Ishida et al, 2021b). Specifically, one aspect of an athlete monitoring program is aimed at quantifying dose-response relationships in order to manage fatigue and to improve training efficacy during the competitive season (Halson, 2014;Gabbett et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The GNSS devices have been used to quantify external TL, including the TL of soccer match play, which have been associated with acute muscle damage and the alterations in neuromuscular performance (de Hoyo et al, 2016;Russell et al, 2016;Coppalle et al, 2019;Wiig et al, 2019;Ishida et al, 2021a). Ishida et al (2021b) reported the strong negative correlations between the changes in loaded CMJ, peak power (PP), and total running distance (p = 0.02, r = 0.65) at 12 h post-match in the NCAA female soccer players. Therefore, the assessment and manipulation of TL using GNSS can be beneficial for maximizing neuromuscular performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations